2014
DOI: 10.1515/fman-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Is Sustainable Development an Issue for Quality Management?

Abstract: Abstract:In recent years, sustainable development strategy for enterprises has become an important issue around the globe. This requires the organization to review its current systems to improve the overall triple bottom-line performance (i.e. economic, environmental, and social). Rising to these challenges requires transforming management system towards sustainable management. Assuming quality management (QM) impact on organisations will continue, what types of QM-based improvement initiatives will develop in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The findings reveal a positive connection between total quality Impact of total quality management (TQM) practices on sustainability and organisational performance management and sustainability. In the literature, the outcomes of this study showed the importance of TQM and its impact on sustainability (Elhuni, 2014;Abusa, 2011, Tena et al, 2001, Jasiulewicz Kaczmarek, 2014, Mendez & Vila-Alonso, 2018. The findings also reveal a significant link between total quality management and performance of an organisation.…”
Section: Discussionsupporting
confidence: 51%
“…The findings reveal a positive connection between total quality Impact of total quality management (TQM) practices on sustainability and organisational performance management and sustainability. In the literature, the outcomes of this study showed the importance of TQM and its impact on sustainability (Elhuni, 2014;Abusa, 2011, Tena et al, 2001, Jasiulewicz Kaczmarek, 2014, Mendez & Vila-Alonso, 2018. The findings also reveal a significant link between total quality management and performance of an organisation.…”
Section: Discussionsupporting
confidence: 51%
“…Among these frameworks, the EFQM excellence model, which is one of the most used business excellence model across European organisations (Araújo and Sampaio, 2014), provides best practices to take into account the impact that organisational activity has on society and to balance the needs of different stakeholders (McAdam and Leonard, 2003; Asif et al , 2011). Moreover, Jasiulewicz-Kaczmarek (2014) found that the literature acknowledges that the approaches based on business excellence models, such as the EFQM model, are used by organisations for the integration of CSR into business processes. In this regards, representative papers may be Tokarcikova et al (2014), who considered the EFQM model to be one of the most commonly used methods for evaluating CSR; Olaru et al (2011) showed that how specific values of CSR are comprised into the EFQM excellence model; or Avlonas and Swannick (2009), who exhibited how organisations adopting the EFQM model are more likely to increase value for stakeholders that those not adopting the model.…”
Section: Introductionmentioning
confidence: 99%
“…That can ultimately have a positive impact on the running and sustainability of the business. To achieve sustainability in an enterprise it is necessary to focus not only on the results of the enterprise but also on its processes [21] [34]. The results of many studies [51] [40] indicate that the best management principles, models, and practices are those that positively contribute to sustainable development.…”
Section: Theoretical Background Of Quality Management Practicesmentioning
confidence: 99%